(3JfhjQ GdeWGdY hJHUjQ GdoeWGdYs - (3GdOhGfi hLdGd GdOjf eMeO Hf CSYOs; (3GdSQGL GdGQehj , eMehO Hf CHj HcQ Hf CMeO, SQGL GdOjf CHh GdKfGA,J (B682 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi GWdY ef eWGdY GdHQGgjf dhGeY CfhGQ Gdjbjf s
(3BNQgG (B:s
(3GdeYdhe ai GdJYQja dci hdcf Gdeaghe HCf GdYde s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3GdfSNI HgG MhGTs
(3Hg WeSs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B166 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B155s
Keywords: (3GdadSaI hGdefWbs